2007
DOI: 10.1007/s00467-007-0451-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and “new” cardiovascular risk markers and factors in pediatric dialysis patients

Abstract: Cardiovascular disease (CVD) is the principal cause of mortality in patients with end-stage renal disease (ESRD). The aim of this study was to analyze carotid intima-media thickness (cIMT), endothelium-dependent dilatation (EDD), and left ventricular mass index (LVMI) as the cardiovascular risk markers and to investigate the independent risk factors of these markers in pediatric dialysis patients. This study included 39 children and adolescents undergoing dialysis (15 hemodialysis and 24 peritoneal dialysis) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 39 publications
5
45
1
1
Order By: Relevance
“…Elevated serum concentrations of CRP is another marker used to stratify CV risk by reflecting chronic inflammation in adult and pediatric CKD and dialysis patients (9,(21)(22)(23). Both CIMT and CRP are found to be elevated in pediatric and adult dialysis patients in recent studies (24)(25)(26)(27). In our study, although CIMT was not different between groups, correlation analysis yielded CRP and age to be independent determinants of CIMT in high transport group.…”
Section: Discussionsupporting
confidence: 39%
“…Elevated serum concentrations of CRP is another marker used to stratify CV risk by reflecting chronic inflammation in adult and pediatric CKD and dialysis patients (9,(21)(22)(23). Both CIMT and CRP are found to be elevated in pediatric and adult dialysis patients in recent studies (24)(25)(26)(27). In our study, although CIMT was not different between groups, correlation analysis yielded CRP and age to be independent determinants of CIMT in high transport group.…”
Section: Discussionsupporting
confidence: 39%
“…A retrospective study of 64 pediatric long-term dialysis patients found that, by multivariate logistic regression analysis, higher systolic BP remained in the final model as an independent predictor of left ventricular hypertrophy with a borderline level of significance (18). Similarly, a recent study of 39 Turkish pediatric long-term dialysis patients found systolic hypertension to be an independent risk factor for increased left ventricular mass index, and diastolic hypertension to be a predictor of carotid intima-media thickness (19).…”
Section: Discussionmentioning
confidence: 98%
“…Hypertension is a risk factor for cardiovascular disease in adult and pediatric ESRD patients (9,(17)(18)(19). A study of 432 adult ESRD patients found that each 10 mmHg rise in mean arterial BP was independently associated with presence of concentric left ventricular hypertrophy, change in left ventricular mass index, change in cavity volume, and development of de novo cardiac failure and ischemic heart disease on follow-up echocardiography (17).…”
Section: Discussionmentioning
confidence: 99%
“…Increased LVMI is defined as an increase in the mass of the left ventricle, which can be secondary to an increase in wall thickness, an increase in cavity size, or both. This increase in mass predominantly results from a chronic increase in the afterload of the left ventricle caused by hypertension and/or by chronic volume load (23)(24)(25). Aortic annulus diameter enlargement has been reported in children with hypertension other than Turner and Marfan syndromes (26,27).…”
Section: Discussionmentioning
confidence: 99%